2012
DOI: 10.1016/j.sbspro.2012.10.168
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach to Analyze Gesture Forms and Functions in Spontaneous Oral Discourse Production of Normal Speakers

Abstract: openAccessArticle: TruePage Range: 242-242doi: 10.1016/j.sbspro.2012.10.168Harvest Date: 2016-01-12 15:11:40issueName: 50th Academy of Aphasia Proceedings.cover date: 2012-10-18pubType

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Kong et al (2012) reported a novel approach to independently analyze gesture forms and functions in spontaneous oral discourse. It was found that about one third of normal speakers did not use any gestures.…”
Section: Introductionmentioning
confidence: 99%
“…Kong et al (2012) reported a novel approach to independently analyze gesture forms and functions in spontaneous oral discourse. It was found that about one third of normal speakers did not use any gestures.…”
Section: Introductionmentioning
confidence: 99%